2014
DOI: 10.1149/2.0051501jss
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Barrier, Etch Stop, and Metal Capping Materials for State of the Art and beyond Metal Interconnects

Abstract: Over the past decade, the primary focus for improving the performance of nano-electronic metal interconnect structures has been to reduce the impact of resistance-capacitance (RC) delays via utilizing insulating dielectrics with ever lower values of dielectric permittivity. The integration and implementation of such low dielectric constant (i.e. low-k) materials has been fraught with numerous challenges. For intermetal and interlayer (ILD) low-k dielectrics, these challenges have been largely associated to int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
115
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 131 publications
(121 citation statements)
references
References 517 publications
1
115
0
Order By: Relevance
“…118 In CMOS logic, memory, NEM and other microelectronic device applications, a-SiN:H is instead more commonly utilized either as a dielectric diffusion barrier, etch stop, or hermetic encapsulation layer. 119,120 To compare and contrast the above materials, their full spectrum of thermal, mechanical, electrical, optical, and chemical properties was measured. The thermal properties investigated include thermal conductivity (κ) and interfacial thermal resistance, as measured by time domain thermoreflectance (TDTR), and coefficient of thermal expansion (CTE) as determined by heated wafer curvature and X-ray reflectivity (XRR) thickness measurements.…”
Section: Ecs Journal Of Solid State Science and Technology 6 (10) N1mentioning
confidence: 99%
“…118 In CMOS logic, memory, NEM and other microelectronic device applications, a-SiN:H is instead more commonly utilized either as a dielectric diffusion barrier, etch stop, or hermetic encapsulation layer. 119,120 To compare and contrast the above materials, their full spectrum of thermal, mechanical, electrical, optical, and chemical properties was measured. The thermal properties investigated include thermal conductivity (κ) and interfacial thermal resistance, as measured by time domain thermoreflectance (TDTR), and coefficient of thermal expansion (CTE) as determined by heated wafer curvature and X-ray reflectivity (XRR) thickness measurements.…”
Section: Ecs Journal Of Solid State Science and Technology 6 (10) N1mentioning
confidence: 99%
“…It was found that this effect is driven primarily by the plasma gas residence time, with a shorter residence time leading to a reduction in re-deposition effects and yielding films of higher purity and improved quality. A report of note 96 incorporated ab initio techniques into theoretical models to examine the effects of PE-ALD reaction mechanisms on precursor adsorption and decomposition pathways for a variety of inorganic and organic Si precursors, including SiH 4 , SiH 2 Cl 2 , SiH 2 (CH 3 ) 2 , (Si 3 N 4 ) 4 (NH 3 ) 12 , and SiN 2 C 8 H 22 . The techniques employed realistic cluster models of aminecovered surfaces to derive the configurations and energies of chemisorption and reaction of these Si sources via functional groups removal.…”
Section: Atomic Layer Deposition (Ald)mentioning
confidence: 99%
“…Particularly, the formed film could fill the non-flat aluminum surface. The existence of nano-pores 4 should be evaluated, when this film is expected for the low k applications. The grain boundary was not observed in this figure.…”
Section: P444mentioning
confidence: 99%
“…Additionally, the SiC x N y O z film is widely studied for developing the highly functional films of low k, diffusion barrier, cupper capping layer and etch stop, for the advanced electronics device fabrication. [4][5][6][7] Its demand is expected to increase further. For producing the SiC x N y O z film at room temperature, the plasmaenhanced CVD (PECVD) process developed in our previous study 8 is expected to be useful, because it forms a silicon carbide (SiC) film from the monomethylsilane (MMS) gas without any heating assistance.…”
mentioning
confidence: 99%